Tinjauan Yuridis Gugatan Citizen Lawsuit Terhadap Pengalihfungsian Cagar Budaya Lapangan Merdeka oleh Pemko Medan (Studi Kasus No 756/PDT.G/2020/PN MDN) - Bagas Apria Dwi; Muklis Muklis (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Since culture is an integral part of human beings, we often think of culture as being passed down from generation to generation. Customs, language, religion, politics, tools, clothing, houses, and artworks are some of the components of a complex culture. A work plan designed to support the preservation of cultural heritage, including maintenance, is called cultural heritage preservation planning. In this research, normative legal research methods are used. This research looks at legislation and secondary sources such as books, theses, scientific journals, and articles. One of the objectives of this research approach is to use a statutory approach. The plaintiffs believed that the government should maintain the credibility and authenticity of the historical location for the public interest. In addition, the purpose of the lawsuit was to prevent the function of Merdeka Square, which was considered detrimental to the community, from being diverted. The ruling recognizes the principle of citizen lawsuit as a citizen's right of action. This principle allows a person or citizen to act in the general interest of citizens or the public interest, including in cases where the defendant files a lawsuit against government actions deemed unlawful. The panel of judges rejected the defendant's exception due to this principle.